Tactile Sensors: Multi‐Layered, Hierarchical Fabric‐Based Tactile Sensors with High Sensitivity and Linearity in Ultrawide Pressure Range (Adv. Funct. Mater. 35/2019). (26th August 2019) - Pyo, Soonjae; Lee, Jaeyong; Kim, Wondo; Jo, Eunhwan; Kim, Jongbaeg
Abstract : In article number 1902484, Jongbaeg Kim and co‐workers develop a highly sensitive, flexible tactile sensor composed of stacked carbon nanotube‐ and Ni‐coated fabrics. With a scalable and cost‐effective fabrication technique, this conceptually simple yet powerful approach not only efficiently utilizes the excellent properties of fabrics but also achieves high sensitivity and linearity over an extremely wide pressure range. This sensor is a promising candidate for tactile interfaces capable of delivering tactile information.